Impact of the voids on the cracking behavior of the duplex oxide scale on the 18%Cr austenite alloy surface. (February 2020) - Yan, Jingbo; Qiu, Yike; Da, Bo; Li, Zeyuan; Li, Yefei; Ding, Zejun; Ma, Lifeng; Zhang, Peng; Yuan, Yong; Gu, Y
Highlights: The cracking tendency of void-containing duplex oxide layer was underestimated. The duplex layer with interface voids will form during the 18%Cr alloys oxidation. The interface exhibits better cracking resistance than the outer Fe3 O layer. Comparing to voids spacing, the radius brings higher impact on the scale cracking. Larger interface voids diameters induces smaller temperature drop of oxide cracking. Abstract: This work investigated the oxide cracking behavior of 18%Cr austenitic steels. The role of voids at the duplex oxide layer interface has been discussed. Simulation results demonstrate that the stress concentration facilitates the crack nucleation at the void top. Interestingly, the interface of the duplex oxide layer exhibits better cracking resistance. Experiment results confirm that the voids facilitate cracking when the temperature drop is beyond 119 °C during oxidizing at 650 °C for TP347H alloy. By comparing, more than 290 °C of temperature drop is needed for the cracking on TP347HFG alloy, which is because the void diameter is small.